2004
DOI: 10.1210/jc.2003-032061
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Subclinical Hypothyroidism in Patients Older than 55 Years: An Analysis of Natural Course and Risk Factors for the Development of Overt Thyroid Failure

Abstract: We aimed to analyze the natural course of subclinical hypothyroidism, quantify the incidence rate of overt hypothyroidism, and evaluate the risk factors for the development of definitive thyroid failure in elderly patients. One hundred seven patients (93 women and 14 men) over age 55 yr with subclinical hypothyroidism and no previous history of thyroid disease were prospectively studied. Subjects were followed up for 6-72 months (mean, 31.7 months) with repeated determinations of TSH and free T(4). Twenty-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
163
2
13

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 240 publications
(199 citation statements)
references
References 30 publications
21
163
2
13
Order By: Relevance
“…We necessitate further research to verify our findings and hypothesis Nearly half of our individuals with mild SCH (49.7%) experienced a normalization of thyroid function during a 3-year period in our study. The rate of spontaneous normalization in this study was similar to that reported in Japan (53.5% over 4.2 years), but was higher than rates reported in the USA (35% over 2 years) [6], Brazil (22.8% over 5 years) [7] and Spain (37.4% over 0.5-6 years) [10]. Huber et al [11] even reported a 4% rate of regression in a population that included patients with diagnosed thyroid diseases.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…We necessitate further research to verify our findings and hypothesis Nearly half of our individuals with mild SCH (49.7%) experienced a normalization of thyroid function during a 3-year period in our study. The rate of spontaneous normalization in this study was similar to that reported in Japan (53.5% over 4.2 years), but was higher than rates reported in the USA (35% over 2 years) [6], Brazil (22.8% over 5 years) [7] and Spain (37.4% over 0.5-6 years) [10]. Huber et al [11] even reported a 4% rate of regression in a population that included patients with diagnosed thyroid diseases.…”
Section: Discussionsupporting
confidence: 84%
“…Although these results are less comparable because of different characteristics of participants in the different studies, we found a regression rate higher than most previous studies in our study, which was the only one to enroll only patients with mild SCH from both sexes. Based on previous studies and expert reviews, we used 7.0 mIU/L of TSH as cut-off points [1,13] and found that higher TSH concentrations significantly impaired the likelihood of TSH normalization in our logistic regression analysis, similar to previous studies [6,8,10]. Accordingly, the generally lower TSH levels among our cases compared with previous studies may be one of the reasons that TSH normalization occurred in a high proportion of our patients.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations